2000
DOI: 10.1002/1097-4644(20010301)80:3<346::aid-jcb70>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in phosphorylation of human and chicken stathmin by MAP kinase

Abstract: Stathmin/Op18 is a highly conserved 19 kDa cytosolic phosphoprotein. Human and chicken stathmin share 93% identity with only 11 amino acid substitutions. One of the substituted amino acids is serine 25, which is a glycine in chicken stathmin. In human stathmin, serine 25 is the main phosphorylation site for MAP kinase. In this study, we have compared the phosphorylation of human and chicken stathmin. The proteins were expressed in Sf9 cells using the baculovirus expression system and purified for in vitro phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Phosphorylated Op18, which increases during mitosis, results in a reduced affinity of Op18 for tubulin and increased microtubule stabilization, thus allowing the mitotic spindle to form (9). Op18 is variably phosphorylated on four distinct serine residues (Ser-16, Ser-25, Ser-38, and Ser-63) in intact cells by different kinases during the cell cycle (10).…”
Section: Molecular and Cellular Proteomics 2:107-116 2003mentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylated Op18, which increases during mitosis, results in a reduced affinity of Op18 for tubulin and increased microtubule stabilization, thus allowing the mitotic spindle to form (9). Op18 is variably phosphorylated on four distinct serine residues (Ser-16, Ser-25, Ser-38, and Ser-63) in intact cells by different kinases during the cell cycle (10).…”
Section: Molecular and Cellular Proteomics 2:107-116 2003mentioning
confidence: 99%
“…For example, transcription factors (E2F, AP-2, and Sp1) can increase Op18 expression (38), whereas p53 appears to repress the Op18 expression (43). Protein kinases such as cyclin-dependent kinases (CDKs), the cAMP-dependent protein kinase, the mitogen-activated protein/extracellular signal-regulated kinase family, and the Ca 2ϩ /calmodulin-dependent kinase IV/Gr can cause extensive phosphorylation of Op18 protein indicating that Op18 can be influenced by a number of signal transduction pathways (10). We found that the mRNA expression of the transcription factor E2F5 and the protein kinase CDK2 were strongly correlated with Op18 mRNA levels in poorly differentiated bronchial derived adenocarcinomas.…”
Section: Op18 Expression In Lung Adenocarcinomasmentioning
confidence: 99%
“…Further, phosphorylation at Ser-25 of stathmin may be due to activation of the MAPK signaling pathway and its phosphorylation may be mediated by MAPK. 26) Consistent with this idea, it has been reported that the MAPK signaling pathway can be significantly activated by some conditions, which include anticancer agent treatment such as etoposide treatment in HeLa cells, 27) while this pathway is constitutively inactivated in JURKAT cells. 28) Collectively, these observations suggest that upregulated expression and increased phosphorylation at Ser-25 of stathmin might be mediated by the MAPK signaling pathway, which is mediated by the cdk2 activation during the onset of etoposide-induced apoptotic events in HeLa cells.…”
Section: Fig 3 Ms Analysis Of Two Different Proteins By Maldi-tof Mmentioning
confidence: 74%
“…Anti-phosphopeptide antibodies stained COS-7 cells transfected with wild-type SCG10 (which is known to be phosphorylated in COS cells) but not COS-7 cells transfected with either stathmin or phosphorylation-site mutant forms of SCG10 (Antonsson et al, 1998). In immunoblots, there was no cross-reactivity with the recombinant protein SCG10 produced in Escherichia coli (N-terminally truncated form) or with stathmin expressed in COS-7 cells or purified from E. coli or baculovirus (Antonsson et al, 2001). SCG10 phospho-antibodies were used at 1:50 for immunocytochemistry and at 1:2500 for Western blots.…”
Section: Methodsmentioning
confidence: 99%